Trying to make sense of the Trojan Horse incident: using historical documents to prompt discussion of politically sensitive issues in secondary schools in Cape Town - Geschier, Sofie M M A (Centre for Applied Language and Literacy Studies and Services in Africa, 2015)
In this qualitative research, I hoped to get some impression of ways teachers and learners in five Cape Town schools deal with the process of making sense of a violent past. I offered five teachers material on the Trojan Horse Incident, partly generated by the TRC, and pondered the questions what for them and their learners is politically sensitive and how they position the people involved in the incident and how they position themselves. I understand by 'politically sensitive issues', issues centering on political and social divisions of the past and their ramifications in the present in this country. Applying a 'Foucaultian' approach to discourse analysis, I used the concepts 'indescribable' and 'undiscussable' as structuring categories, next to a differentiation between the discourse of classroom talk, and informal discourses outside the classroom situation. I also differentiated between the sense making processes of teachers, being part of a generation that lived through Apartheid, and of learners, the 'new' generation who didn't have that experience. The results of this research are: Firstly, teachers and learners in the five schools positioned themselves, the people involved in the incident and the researcher through dynamic practices of in- and excluding (shifting between 'us' and 'them') and of past and present framing (shifting between past and present tenses). Both groups seem to prefer to position themselves as 'observers'. In most classes, most of the time was spent on how exactly the Trojan Horse Incident took place (when, where, which tactics the policemen used, consequences,). Moral questions ('why' questions) were left for the end of the period or left implicit. Secondly, there was not a lot of space during classroom interactions for emotions and personal stories. The power/knowledge structure of the discourse of schooling seemed to be very strong, although it was also a matter of personal choices by teachers and learners. An 'official' image of Apartheid, with clear differentiations between victims and perpetrators prevailed. Personal stories were only situated in formal discourses of schooling before or after the actual lesson (learners speaking with the teacher about their personal experiences of or reactions to violence) or when 'others' were present, be it learners from 'another' community than the majority of learners and the teacher, or be it the researcher. Thirdly, a discourse of reconstructing personal histories and identities had more space in informal discourses (for example learners talking to one another during breaks) and during interviews with me. South African youth might have (similar to German and Irish youth) a 'fatigue' towards 'official', 'consensus' knowledge of the past and they might not to be able or not want to make sense of the 'wall' of silenced personal stories of those who have experienced the conflicts in the past. Fourthly, 'sensitive issues' were mostly expressed outside the classroom interactions. These were violence in past and present; moral stances towards violence and responsibility; schooling (teaching but also disciplining); and stereotypes people have of 'other' South Africans and the separate lives they have.